Perceptions of Junior High School Students in Kecamatan Talang Empat, Bengkulu Tengah on the Implementation of Physical Education Learning during the Covid-19 Pandemic - Sugiyan Fauzi; Citra Dewi; Supriyanto Supriyanto (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the perceptions of junior high school students in Talang Empat District, Central Bengkulu Bengkulu Province towards the implementation of physical education learning during the covid-19 pandemic. This type of research is descriptive quantitative with survey method. While the data collection techniques using questionnaires and data analysis techniques using descriptive statistics with percentages. The population in this study amounted to 116 students and a sample of 23 students. The results of the research on the perceptions of junior high school students in Talang Empat District, Central Bengkulu, on the implementation of physical education learning during the COVID-19 pandemic, were in the very positive category 4.34% or 1 student, positive category 30.43% or 7 students, moderate category 34.78 % or 8 students, negative category 21.73% or 5 students, and very negative category 8.69% or 2 students. The results stated that the perception of junior high school students in the Talang Empat sub-district, Central Bengkulu, towards the implementation of physical education learning during the COVID-19 pandemic was stated to be moderate.